Comparison and Application of Advocacy Issues in the Context of Majallah Al-Aḥkām Al-‘Adaliya and Pakistani Law - Zia ur Rahman; Niaz Muhammad; Karim Dad (Journal of Islamic and Religious Studies, 2020)
The Islamic Shari’ah has ensured and guaranteed protection and security of life, wealth, and honor through the imposition of different laws and injunctions. Alongside this, it permitted the jurists of the Ummah to frame and promulgate laws for their security under the Quran & Sunnah, which are the primary sources of Shari’ah. The Muslim scholars authored jurisprudence books keeping in view the need for the time in every era and thus a vast compilation of Islamic literature came into existence. The Ottoman Caliphate enjoys a particular background and characteristics among different Muslim empires. The said Caliphate not only had very extensive geographical boundaries but also had links with the contemporary governments. This Caliphate, following Fiqh Ḥanafī, had formed Majallah al Aḥkām al ‘Adaliyah for the country’s economic system. The clauses of Majallah were based on deep-rooted thoughts and, therefore, caused a great impact on the succeeding assets and heritage of jurisprudence. In this article, after mentioning the introduction of Majallah Al-Aḥkām Al-‘Adliyah and its methodology, a comparative and applied review of the selected provisions of "Kitāb Al-Wakālah" with "Contract Act 1872" is discussed and finally, the conclusions drawn from this research, along with few recommendations, are mentioned.